Vulnerable Road Users or Vulnerable Transport Planning? - Khayesi, Meleckidzedeck (Frontiers in Sustainable Cities, 2020)
This paper subjects the concept of vulnerable road users, which states that walkers and cyclists are easily injured and killed in a car-dominated road space, to a critical analysis. The paper finds this term wanting because research and practice shows that the real vulnerability lies within transport planning that gives in to influences that are more focused on the needs of motorized transport. The paper proposes the concept of vulnerable transport planning to underscore the fact that transport planning often lacks inclusion and is influenced by forces that favour motor vehicles. This influence leads to omission and neglect of walkers, cyclists, children, disabled persons, the elderly and highway-adjacent communities in transport and land-use planning.